Pengaruh Perbedaan Waktu Perendaman pada Alat Tangkap Jaring Insang (Gill Net) terhadap Hasil Tangkapan Ikan Kembung (Rastrelliger) di Perairan Bluru Kidul Sidoarjo - Tasya Amalia; Yusrudin Yusrudin; Sumaryam Sumaryam (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Bluru Kidul Village is an area located near the northeastern coast of Sidoarjo, where its geographical position provides significant benefits for the community. Consequently, the majority of residents work as fishermen and live side by side with the marine ecosystem. Due to the existence of Bluru Kidul Village, Sidoarjo City is often referred to as a fisheries or coastal city. The fish resources in these waters are dominated by small pelagic fish, large pelagic fish, and demersal fish. One of the most widely used fishing gears is the gill net. This study applied treatments with soaking durations of 2 hours, 3 hours, and 4 hours. The objectives of this research were to identify the composition of gill net catches, analyze the effect of different soaking times on gill net catches, and determine the optimal soaking duration for catching Indian mackerel (Rastrelliger) using gill nets. Data analysis was conducted using statistical methods, including analysis of variance (ANOVA) and normality tests to ensure data suitability. To determine whether soaking duration had a significant effect, a further statistical test, namely the Least Significant Difference (LSD) test, was applied to identify which soaking time produced the best catch of Indian mackerel. The results indicated that there were significant differences in catch variables between the 4-hour treatment and the 3-hour and 2-hour treatments, whereas the difference between the 3-hour and 2-hour treatments was not significant. This finding demonstrates that the 4-hour soaking duration resulted in significantly different catch outcomes compared to the 3-hour and 2-hour durations, but no significant difference was observed between the 3-hour and 2-hour treatments.